(untitled) (Bangladesh Heart Journal, 2021)
Background: The risk of coronary artery disease in women after menopause sharply rises in contrast to that of women before menopause because of hormonal protection against atherosclerosis. No research work has been done so far to see the angiographic pattern and severity of coronary artery disease in premenopausal women and their comparison with those of postmenopausal women. This study will help understand the pattern and severity of CAD both in premenopausal and postmenopausal women. Methods: This cross sectional analytical study was conducted over 100 ACS female patients who were purposively selected and agreed to do coronary angiogram during index hospital admission. Among them 50 patients were premenopausal status with CAD constituted study group I and another 50 postmenopausal women with CAD constituted study group II. The main objective of the study was to compare the angiographic severity of coronary artery disease between premenopausal and postmenopausal women with acute coronary syndrome. Angiographic severity of CAD was assessed by vessel score, Gensini score and Friesinger score. Results: LAD was the common artery involved (76% vs. 56%) followed by RCA (72% vs. 36%) and LCX (62% vs. 30%) in group-II compared to group-I and involvement of individual coronary artery was statistically significant (P values were 0.03, 0.003 and 0.001 respectively). Critical stenosis (70-99%) involving the all three major epicardial vessels (LAD, LCX and RCA) were found most frequently in group-II and the percentage of lesions were 56% vs. 30%; 56% vs. 22% and 54% vs. 22% respectively (p< 0.05). The vessel score of the study patients revealed that singe vessel involvement was significantly higher in group-I (52% vs. 24%) (p=0.003) and triple vessel involvement was found significantly higher in group-II (40% vs. 12%) (p=0.001). Severity assessment by Friesinger score showed normal (0) and low (1-4) Friesinger score significantly higher in group-I patients (P=0.04 and P=0.007 respectively) and high Friesinger score (11-15) was found significantly higher in patients in group II (p=0.001). Severity assessment by Gensini score of the study patients revealed significantly higher mild Gensini score in group-I patients (P=0.002) and severe Gensini score in group II patients (p=0.002). Conclusion: Coronary artery disease is one of the major important problems not only in postmenopausal women but in premenopausal women also. Postmenopausal women suffer from more triple vessels involvement, more diffuse and severe disease. This study results point out that premenopausal women suffer from less severe coronary artery disease and there is a trend to involve mid LAD more frequently in comparison to other two major coronary arteries and LM coronary artery in comparison to postmenopausal women. Bangladesh Heart Journal 2021; 36(2): 113-123